Design of Automatic Attendance System Using RFID and ESP32 Based on Internet of Things (IoT) - Febriana, Lutfi Afudn; Aji, Wahyu Sapto (Signal and Image Processing Letters, 2024)
The development of RFID technology in the field of education is quite interesting, including the implementation of an automated presence system that is integrated with the database that supports the processing of information about the presence of lectures. The app consists of several major components, such as an RFID Tag, an RFID Reader, and the ESP32 microcontroller. RFID Tags are used to read data and serve as student IDs. This tool system is integrated into the website according to the concept of the Internet of Things. This concept is the communication between the tool system and the website; data is automatically stored directly into the database that has been provided. The mode used by the presence system consists of two modes, namely list mode and presence mode. The functionality of the system hardware and software has been tested to ensure that the tools and components work properly and can function as required. The test results showed that the distance required to be able to read RFID Tags was 0 to 2.5 cm, the read time of an RFID Tag was an average of 2.39 seconds, and the update time of website data was 3.33 seconds. The performance of the system in testing failed to read an RFID Tag three times, with a success rate of 85.71%.